Study the Doping Effect of Lead(Pb) on the Optical Properties of Cadmium Sulfide (CdS) Thin Films. - Abdul-Majeed E.Ibrahim; Raid A.Ismail; Wattban N. Nada (Tikrit Journal of Pure Science, 2023)
The optical properties of pure and doped  Cadmium Sulfide thin films have been stadied  in  the present work. Cadimum Sulfide can be doped by the Lead of (5%,10%,15%,20%) which prepared by chemical spray pyrolysis technique were deposited on (350ºC) glass substrates. The optical properties– Trasmittance (T), Absorbtance (A), Energy band gap (Eg), Absorption coefficient(α) and Extinction Coefficient (ko) - within wave length range (330-1100)nm. The cadmium sulfide (pure) thin flims were found to exhibit hight trnsmittance abute (82-86)%, the transmittance decreases with the increasing the doped ratio by the lead(Pb).The direct band gap energy of films decreases from (2.40eV) for the pure thin films to (2.35,2.31,2.25,2.19 eV) for  the doped by lead at (5%,10%,15%,20%).